THE INFLUENCE OF FINANCIAL TARGETS, NATURE OF INDUSTRY, CHANGE OF DIRECTORS AND CEO POLITICIANS ON FRAUDULENT FINANCIAL STATEMENTS - Harry Budiantoro; Cahyo Adi Nugroho; Perdana Wahyu Santosa; Kanaya Lapae (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims to examine the influence of financial targets, nature of industry, change of directors and ceo politicians on fraudulent financial statements. This study uses a sample of state-owned companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The sampling technique in this study is purposive sampling and can be a sample of 17 companies. This study uses secondary data, namely the company's financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). The analytical method used is multiple linear regression. The results of this study indicate that financial targets have a significant positive effect on financial statements. The nature of the lindustry has a negative effect on the financial statements. Changes that have a negative financial effect on reporting fraud. CEO Politicians have no effect on financial statements.